Nanostructures from Self‐Assembling Triazine Tertiary Amine N‐Oxide Amphiphiles. Issue 17 (7th November 2013) - Beecham, Matthew P.; Clarkson, Guy J.; Hall, Gareth; Marsh, Andrew
Abstract A new set of amphiphilic tertiary amine N‐oxides has been prepared and their self‐assembly properties observed in aqueous solution by tensiometry, dynamic and static light scattering. X‐ray crystallographic analysis of parent amines and sulfoxide congeners indicates the formation of hydrogen‐bonded dimers as the primary assembly unit for formation of vesicles in preference to the compact micelles typical of lauryl dimethylamine N‐oxide (LDAO). 6‐Benzyloxy‐N, N′‐bis(5‐diethylaminopentylamine oxide)[1, 3, 5]triazine‐2, 4‐diamine forms a 1 μm vesicle observed to entrap fluorescein. The [1, 3, 5]triazine core thus allows variation of the new self‐assembled structures from nano‐ to micrometre length scales.